MENIMBANG KEISTIMEWAAN SEKOLAH MENUJU IDEALITAS SISTEM PENDIDIKAN (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2002)
The meening of education has been narrowed to be school system, so those who da not go to school are considered as uneducated people. It distorts the substance of the meaning of education, indeed it results in the exclusion of same national generation that, by chance. come from out of school system to take part in national constellation. Therefore, many criticisms are addressed to school system, as written by Reinner in hi's School is Dead'. Yet, those crititisms do not bring about significant changes, because people, have been addicted to school system that gels muih privilege from the government. Thin artide tries to offer a change in educational system by removing the privilege from school.